Otoritas Manajemen Mutu Madrasah di Era Otonomi - Nawawi Nawawi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Its really a complicated matter to find solution aout madrasah’s position. Various problem which emerge before a period of autonomy, not yet completed, added by new problem which always emerge one another. By otonomization of madrasah institute, madrasahhave to be given the authority to arrange its own bussiness; improving its human resource and managing effort to financing institute self-supportingly, not depended to institute National Religion Departement. Madrasah (state) is under authority of district’s Religion Departement, the duty is only limited to observation structurally and have no authority to intervence the institute. To realize it, madrasah have to apply total quality management to face the free competition.